Cellular dehydration acutely degrades mood mainly in women: a counterbalanced, crossover trial. Issue 10 (28th May 2021) - Suh, HyunGyu; Lieberman, Harris R.; Jansen, Lisa T.; Colburn, Abigail T.; Adams, J. D.; Seal, Adam D.; Butts, Cory L.; Kirkland, Tracie M.; Melander, Olle; Vanhaecke, Tiphaine; Dolci, Alberto; Lemetais, Guillaume; et al.
Abstract: It is unclear if mild-to-moderate dehydration independently affects mood without confounders like heat exposure or exercise. This study examined the acute effect of cellular dehydration on mood. Forty-nine adults (55 % female, age 39 (sd 8) years) were assigned to counterbalanced, crossover trials. Intracellular dehydration was induced with 2-h (0·1 ml/kg per min) 3 % hypertonic saline (HYPER) infusion or 0·9 % isotonic saline (ISO) as a control. Plasma osmolality increased in HYPER (pre 285 (sd 3), post 305 (sd 4) mmol/kg; P < 0·05) but remained unchanged in ISO (pre 285 (sd 3), post 288 (sd 3) mmol/kg; P > 0·05). Mood was assessed with the short version of the Profile of Mood States Questionnaire (POMS). The POMS sub-scale (confusion-bewilderment, depression-dejection, fatigue-inertia) increased in HYPER compared with ISO ( P < 0·05). Total mood disturbance score (TMD) assessed by POMS increased from 10·3 (sd 0·9) to 16·6 (sd 1·7) in HYPER ( P < 0·01), but not in ISO ( P > 0·05). When TMD was stratified by sex, the increase in the HYPER trial was significant in females ( P < 0·01) but not in males ( P > 0·05). Following infusion, thirst and copeptin (surrogate for vasopressin) were also higher in females than in males (21·3 (sd 2·0), 14·1 (sd 1·4) pmol/l; P < 0·01) during HYPER. In conclusion, cellular dehydration acutely degraded specific aspects of mood mainly in women. The mechanisms underlying sex differences may be related to elevated thirst and vasopressin.